Low birth weight and macrosomia in Tigray, Northern Ethiopia: who are the mothers at risk? - Hayelom Gebrekirstos Mengesha; Alem Desta Wuneh; Berhe Weldearegawi; Divya L. Selvakumar (BMC, 2017)
Abstract Background Infant birth weight, which is classified into low birth weight, normal birth weight and macrosomia, is associated with short and long-term health consequences, such as neonatal mortality and chronic disease in life. Macrosomia and low birth weight are double burden problems in developing counties, such as Ethiopia, but the paucity of evidence has made it difficult to assess the extent of this situation. As a result there has been inconsistency in the reported prevalence of low birth weight and macrosomia in Ethiopia. This study aimed to determine the incidence and predictors of low birth weight and macrosomia in Tigray, Northern Ethiopia. Method We conducted a cross-sectional survey among a cohort of 1152 neonates delivered in Tigray Region at randomly selected hospitals between April and July 2014. We used the birth weight category described previously as an outcome variable. Data were collected using structured questionnaire by midwives. We entered and analyzed data using STATA™ Version 11.0. Data were described using a frequency, percentage, relative risk ratio, and 95% confidence interval. Multinomial logistic regression was conducted to identify independent predictors of low birth weight and macrosomia. Result In this study, we found a 10.5% and 6.68% incidence of low birth weight and macrosomia, respectively. Seventy (57.8%) of all low birth weight neonates were term births. The predictors for low birth weight were: early marriage (<18 year) (RRR: 0.59, CI: 0.35-0.97); rural residence (RRR: 0.53, CI: 0.32-0.9); prematurity (RRR: 15.4, CI: 9.18-25.9); no antenatal follow-up (RRR: 6.78, CI: 2.39-19.25); and female sex (RRR: 1.77, CI: 1.13-2.77). Predictors for macrosomia were: female gender (RRR: 0.58, CI: 0.35-0.9); high body mass index (RRR: 5.0, CI: 1.56-16); post-maturity (RRR: 2.23, CI: 1.06-4.6); and no maternal complication (RRR: 0.46, CI: 0.27-0.8). Conclusion In this study, we found gestational age and gender of the neonate to be common risk factors for both low birth weight and macrosomia. Strengthening antenatal follow up, prevention of pre and post maturity, controlling body mass index, and improving socioeconomic status of mothers are recommendations to prevent the double burden (low birth weight and macrosomia) and associated short and long-term consequences.